Redefining education through Anishinaabe pedagogy: a journey to clarify how Aboriginal education brought me to Anishinaabe pedagogy - Chartrand, Rebecca (Canadian Journal of Native Education, 2012)
Using a bifocal, place conscious Anishinaabe-Western/Euro-Canadian lens, the evolution of Aboriginal education is examined from a personal and professional perspective. Meaning surfaces from the lived-experiences of the author, an Anishinaabe woman, educator, parent, community member and Aboriginal education specialist, and what continues to unfold at national, provincial and local levels as “Aboriginal education” with an emphasis on what is taking place in south central Manitoba. The thesis highlights the resurgence of Indigenous ways of knowing, teaching and learning, specifically Anishinaabe pedagogy, and identifies goals for education from an Anishinaabe lens that looks beyond academic success to pedagogical tools that can help restore wellness and well-being for all Canadians. October 2016